The role of enzalutamide in the treatment of castration-resistant prostate cancer. (September 2012) - Rawlinson, Alex; Mohammed, Aza; Miller, Marek; Kunkler, Roger
Prostate cancer is the most common solid organ cancer affecting the male population. Men with metastatic prostate cancer treated with androgen ablation therapy often respond rapidly, with improvement in bone pain and decreases in serum prostate-specific antigen. However, almost all patients progress to the castration-resistant state and abiraterone acetate was the last treatment available with proven survival benefit. Enzalutamide (formerly MDV3100) is an androgen receptor signaling inhibitor that has been shown to improve survival in men with metastatic castration-resistant prostate cancer previously treated with chemotherapy. In this article we discuss the characteristics of enzalutamide and provide a review of its clinical development.